Sosialisasi Penggunaan Pestisida Nabati untuk Para Petani Desa Dongkal, Pedes, Karawang, Jawa Barat - Dene Herwanto; Fadel Mochamad Ismail; Ardiansyah Arum; Pradipta Aurelia; Amanda Salsabila Kusumawardana; Amanda Saqinah; Faradila Linda Rahmawati; Farhan Bagus D; Azelia Mutiara Ramli Ramli; Bintang Abyadh Ramadhan R; Rahma Utami; Dian Juliasari; Siti Jenab; Husnul Khoerun Nissa; Micel Gevanka Tumbelaka; Farrel Achmad Rozan; Putri Permatasari; Imelya Febriyanti (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2024)
Pests are one of the main enemies of farmers in obtaining quality harvests. Currently, pesticides made from chemicals are still the first choice for farmers to eradicate pests. Considering the negative impact of using chemical pesticides, it is necessary to provide outreach to farmers so that they are willing to switch to vegetable pesticides to eradicate pests. This community service activity was carried out in Dongkal Village, which is one of the villages in the Pedes District, Karawang Regency, where farming is the main livelihood of the majority of the population. This activity, which carried out within the framework of Service Community (KKN) subject for students at Universitas Singaperbangsa Karawang, aims to provide understanding and awareness to farmers in Dongkal Village regarding the negative impacts of using chemical pesticides in the long term, as well as socializing the use of vegetable pesticides that are more environmentally friendly and effective in eradicate pests. The outreach activities held in collaboration with the field officer of Agriculture UPTD. At the end of the activity, samples of vegetable pesticides produced by KKN participant were handed over to the Head of the Farmer Group. Besides, training and assistance also provided to farmers on how to make vegetable pesticides so that they can make their own vegetable pesticides in the future.